Non-vasogenic cystoid maculopathies. (November 2022) - Gaudric, Alain; Audo, Isabelle; Vignal, Catherine; Couturier, Aude; Boulanger-Scemama, Élise; Tadayoni, Ramin; Cohen, Salomon Yves
Abstract: Besides cystoid macular edema due to a blood-retinal barrier breakdown, another type of macular cystoid spaces referred to as non-vasogenic cystoid maculopathies (NVCM) may be detected on optical coherence tomography but not on fluorescein angiography. Various causes may disrupt retinal cell cohesion or impair retinal pigment epithelium (RPE) and Müller cell functions in the maintenance of retinal dehydration, resulting in cystoid spaces formation. Tractional causes include vitreomacular traction, epiretinal membranes and myopic foveoschisis. Surgical treatment does not always allow cystoid space resorption. In inherited retinal dystrophies, cystoid spaces may be part of the disease as in X-linked retinoschisis or enhanced S-cone syndrome, or occur occasionally as in bestrophinopathies, retinitis pigmentosa and allied diseases, congenital microphthalmia, choroideremia, gyrate atrophy and Bietti crystalline dystrophy. In macular telangiectasia type 2, cystoid spaces and cavitations do not depend on the fluid leakage from telangiectasia. Various causes affecting RPE function may result in NVCM such as chronic central serous chorioretinopathy and paraneoplastic syndromes. Non-exudative age macular degeneration may also be complicated by intraretinal cystoid spaces in the absence of fluorescein leakage. In these diseases, cystoid spaces occur in a context of retinal cell loss. Various causes of optic atrophy, including open-angle glaucoma, result in microcystoid spaces in the inner nuclear layer due to a retrograde transsynaptic degeneration. Lastly, drug toxicity may also induce cystoid maculopathy. Identifying NVCM on multimodal imaging, including fluorescein angiography if needed, allows guiding the diagnosis of the causative disease and choosing adequate treatment when available. Highlights: Non-vasogenic cystoid maculopathy refers to cystoid spaces without fluorescein leakage. Disturbances in retinal dehydration or intercellular adhesion may cause cystoid spaces. They may be tractional, due to inherited retinal dystrophies, optic atrophy or induced by drug toxicity. They may be due to atrophic age macular degeneration and chronic central serous chorioretinopathy. Identifying cystoid spaces without fluorescein leakage guides the diagnosis and treatment.